Functional asymmetry and electron flow in the bovine respirasome - Sousa, Joana S (eLife, 2016)
Respirasomes are macromolecular assemblies of the respiratory chain complexes I, III and IV in the inner mitochondrial membrane. We determined the structure of supercomplex I(1)III(2)IV(1) from bovine heart mitochondria by cryo-EM at 9 Å resolution. Most protein-protein contacts between complex I, III and IV in the membrane are mediated by supernumerary subunits. Of the two Rieske iron-sulfur cluster domains in the complex III dimer, one is resolved, indicating that this domain is immobile and unable to transfer electrons. The central position of the active complex III monomer between complex I and IV in the respirasome is optimal for accepting reduced quinone from complex I over a short diffusion distance of 11 nm, and delivering reduced cytochrome c to complex IV. The functional asymmetry of complex III provides strong evidence for directed electron flow from complex I to complex IV through the active complex III monomer in the mammalian supercomplex. DOI: http://dx.doi.org/10.7554/eLife.21290.001